Methylation contributes to imbalance of PRDM1α/PRDM1bβ expression in diffuse large B-cell lymphoma. Issue 8 (3rd August 2015) - Zhang, Yi-Wen; Zhang, Jie; Li, Jun; Zhu, Jun-Feng; Yang, Yan-Li; Zhou, Li-Li; Hu, Zhong-Li; Zhang, Feng
Abstract : The positive regulatory domain 1 (PRDM1) exists as two isoforms: PRDM1α and PRDM1β. The former is frequently inactivated, while the latter is overexpressed in a subset of diffuse large B-cell lymphoma (DLBCL). To investigate the possible epigenetic alteration of PRDM1α and PRDM1β expression, the methylation of these two promoter isoforms was assessed in B lymphoma cell lines and DLBCL samples. Hypomethylation of PRDM1β CpG islands was preferentially detected in lymphoma cells. However, both high and low methylation of PRDM1α CpG islands was simultaneously observed in cases of DLBCL compared with the moderate methylation of non-tumor cases. CpG 16–21-specific high methylation was correlated with low expression of PRDM1α in PRDM1β -positive DLBCL samples. Three increased and one decreased miRNAs were significantly different between cases of DLBCL and non-tumor reactive hyperplasia. Thus, our results indicate that aberrant methylation silencing of PRDM1α and hypomethylation activation of PRDM1β are frequent events in DLBCL.